Integrative Approaches in Colon Cancer Management: Combining Conventional Therapies with Novel Strategies - Dabbour, Alaa Faisel A; Albalawi, Abdulaziz Marzoq; Noor, Mohammed; Alanazi, Ibrahim Manzil; Aluhaybi, Omar Awwadah; Almutairi, Fahad; Alharbi, Sameer Mubayrik; S, Alsobhi, Abdulah Fitten; Alsaheli, Yousef Ali; Sahlool, Ahmed Adil (Journal of Posthumanism, 2024)
Colon cancer continues to be a major global health burden, ranking among the leading causes of cancer-related morbidity and mortality. Conventional treatment modalities, including surgery, chemotherapy, and radiotherapy, have significantly improved patient outcomes; however, they are often limited by recurrence, drug resistance, and severe side effects. In recent years, integrative approaches that combine standard therapies with novel strategies have gained momentum, aiming to enhance therapeutic efficacy, reduce toxicity, and promote patient-centered care. Emerging innovations—such as immunotherapy, molecularly targeted drugs, gut microbiome modulation, natural bioactive compounds, and artificial intelligence–driven technologies—offer promising avenues to complement established practices. This review synthesizes current evidence on integrative colon cancer management, comparing the strengths and limitations of conventional and novel approaches, while highlighting the importance of multidisciplinary and personalized treatment frameworks. Ultimately, integrative models hold the potential to transform colon cancer care by bridging traditional and innovative therapies, improving survival rates, and enhancing quality of life for patients.